Genetic diversity and seascape population structure in eelgrass (Zostera marina) meadows in the northwestern Pacific - Seo Yeon Byeon; Kyeonglim Moon; Sun Kyeong Choi; Hee-kyu Choi; Sangil Kim; Ji Hyoun Kang; Sang Rul Park; Hyuk Je Lee (Global Ecology and Conservation)
Seagrasses, the only flowering plants in the ocean, provide numerous, but crucial ecosystem services for coastal and estuarine environments. Yet, natural seagrass populations have been continuously declining worldwide due to ongoing climate change and accelerating anthropogenic influences. To make conservation efforts for effectively managing and preserving local seagrass populations, an understanding of their genetic diversity and population structure is essential. In the present study, using seven microsatellites we assessed the current population genetic status and phylogenetic relationships of Zostera marina, the predominant seagrass species in the northwestern Pacific, on the entire coasts of the Korean Peninsula and Jeju Island and also the northeastern China and southwestern/northern Japan. Results of genetic diversity analysis revealed that Jeju Island populations display the higher degree of asexual reproduction, as indicated by a lower level of clonal diversity, and thus significantly reduced genetic diversity than any other coastal regions. Genetic population structure tended to be grouped into corresponding coastal regions, although two genetic clusters are the most likely, which can be attributed to limited contemporary gene flow occurring among the regional populations. Jeju Island population has a unique genetic composition in reference to the other sea areas, and the possibility of local extinction may be the highest due to the depleted genetic diversity as well as strong genetic differentiation. Our study provides fundamental information on the eelgrass’s genetic diversity and spatial population structure over the northwestern Pacific, which helps to make restoration efforts, including transplantation projects, particularly for the Jeju Island population.